2014
DOI: 10.1016/j.leukres.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Younger adults with acute myeloid leukemia in remission for ≥3 years have a high likelihood of cure: The ECOG experience in over 1200 patients

Abstract: We examined 1229 younger patients with acute myeloid leukemia who achieved CR1 on Eastern Cooperative Oncology Group trials. We defined late relapse as occurring after ≥3 years of CR1. With median follow-up of 11.3 years, there were 14 late relapses (1.1% of CR1 patients; 3.3% of 3-year CR1 patients). Eight achieved second CR and median overall survival after late relapse was 3.2 years. Most patients tested (9/11) had a normal karyotype at diagnosis; none had new cytogenetic abnormalities at relapse. Late rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Late relapse in acute leukaemia is considered relatively uncommon. In acute myeloid leukaemia (AML), approximately 1% of all who achieved complete remission (CR) relapse after 3–5 years 1 , 2 . In acute lymphoblastic leukaemia (ALL), data on late relapses are mostly reported in paediatrics 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Late relapse in acute leukaemia is considered relatively uncommon. In acute myeloid leukaemia (AML), approximately 1% of all who achieved complete remission (CR) relapse after 3–5 years 1 , 2 . In acute lymphoblastic leukaemia (ALL), data on late relapses are mostly reported in paediatrics 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…3 To this end, we recently analyzed Eastern Cooperative Oncology Group (ECOG) data and observed that there were very few relapses in patients who maintained CR1 for at least 3 years (14/1229, 1.1%). 4 Relapses occurring after 3 years from CR1 were considered late (LR), and usually occurred between 3 and 5 years after CR1 (12/14, 86%); two very LRs occurred after 5 years. Interestingly, the majority of LRs (82%) occurred in patients with normal cytogenetics, and no patients had an unfavorable karyotype.…”
mentioning
confidence: 99%
“…We describe four unique cases of LR AML after allo-HCT—one previously reported ECOG case 4 and three new cases from patients treated at the Mayo Clinic. LR after allo-HCT is rare, and, to our knowledge, this is the largest case series of this kind to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Endostatin was discovered in 1997, and was considered one of the most active angiogenesis inhibitors. It can effectively inhibit the growth of endothelial cells, and has been associated with the development and prognosis of malignant tumor diseases (Fung et al, 2013;Watts et al, 2014). FGF-19 belongs to an endocrine subfamily, and it is expressed in the terminal ileum, brain, cartilage, kidney, and other organs; it is important for the metabolism of nutrients.…”
Section: Discussionmentioning
confidence: 99%